1997
DOI: 10.1038/sj.leu.2400819
|View full text |Cite
|
Sign up to set email alerts
|

Deletions at 11q identify a subset of patients with typical CLL who show consistent disease progression and reduced survival

Abstract: Eighty-four patients with typical chronic lymphocytic leukemia 27% of patients with B-CLL. [11][12][13] Fegan et al 13 studied 45 (CLL) (by morphological and immunophenotypic criteria) on patients with typical CLL over 5 years and performed cytowhom karyotypes were available were studied. Binet stage at genetic analysis every 6-12 months or more frequently if there diagnosis and follow-up were defined. Survival was calculated was evidence of disease progression. Abnormalities were from diagnosis. Fifty-one per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
1
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 0 publications
7
67
1
4
Order By: Relevance
“…The use of CGH combined with AP-PCR allowed to detect genetic abnormalities in 79% of cases (15/19) with apparently normal or unsuccessful karyotype ( Table 2). As has been reported in previous studies using FISH, in our series losses of 13q and gains of chromosome 12 were the most frequent changes both by CGH and by AP-PCR [1,[4][5][6][7][8][9][10]. These results were confirmed by FISH.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The use of CGH combined with AP-PCR allowed to detect genetic abnormalities in 79% of cases (15/19) with apparently normal or unsuccessful karyotype ( Table 2). As has been reported in previous studies using FISH, in our series losses of 13q and gains of chromosome 12 were the most frequent changes both by CGH and by AP-PCR [1,[4][5][6][7][8][9][10]. These results were confirmed by FISH.…”
Section: Resultssupporting
confidence: 80%
“…Genetic studies have provided useful information in understanding the pathogenesis of CLL, and some aberrations may also have a prognostic impact [4][5][6][7][8][9][10]. In CLL, accurate and successful cytogenetic analysis has been hindered by the low in vitro mitotic activity of the critical B-cell population with metaphases arising from normal T-cells being frequent.…”
Section: Introductionmentioning
confidence: 99%
“…5,15,16,19,32,36 and 50) with 6q loss detected by FISH or arrayCGH were successfully subjected to 32K tiling path chromosome 6 arrayCGH to more precisely define the smallest commonly deleted region (SCDR). We confirmed that the SCDR included 6q21q32 comprising a 1.4 Mb region (Figure 2).…”
Section: Loss Of 6q and Determination Of The Smallest Commonly Deletementioning
confidence: 99%
“…A subset of genomic aberrations was identified as important independent predictors of disease progression and survival 3 . Deletions of 11q and 17p, affecting the ataxia telangiectasia mutated (ATM) gene and p53 tumor suppressor gene (TP53) respectively, have been associated with disease progression and reduced survival [4][5][6][7] . Early identification of these deletions could allow clinicians to choose appropriate therapy for these patients 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…8 These abnormalities define a subset of typical CLL patients that show consistent disease progression and reduced survival. 9 In a recent study, Stilgenbauer et al 10 characterized deletions and translocations involving chromosome bands 11q21-q23. Using a panel of yeast artificial chromosome (YACs) clones organized as a contig, they were able to define a single critical region of 2-3 Mb where all deletions and translocations clustered and that is encompassed by a single YAC clone.…”
Section: Introductionmentioning
confidence: 99%